2005
DOI: 10.1007/s10038-005-0290-4
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic studies of 20 Japanese families of dystrophic epidermolysis bullosa

Abstract: Dystrophic EB (DEB) is clinically characterized by mucocutaneous blistering in response to minor trauma, followed by scarring and nail dystrophy, and is caused by mutations in the COL7A1 gene encoding type VII collagen. DEB is inherited in either an autosomal dominant (DDEB) or recessive (RDEB) fashion. DDEB basically results from a glycine substitution mutation within the collagenous domain on one COL7A1 allele, while a combination of mutations such as premature stop codon, missense, and splice-site mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…Approximately 300 distinct COL7A1 mutations have been identified in patients with DEB around the world, and the clinical features, severity, prognosis, and response to treatment vary depending on the specific mutation. 15,24,[27][28][29][30][31] Our understanding of how specific mutations produce differing clinical presentations and prognoses is limited. We believe that our systems have the advantage of being able to use human genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 300 distinct COL7A1 mutations have been identified in patients with DEB around the world, and the clinical features, severity, prognosis, and response to treatment vary depending on the specific mutation. 15,24,[27][28][29][30][31] Our understanding of how specific mutations produce differing clinical presentations and prognoses is limited. We believe that our systems have the advantage of being able to use human genes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the COL7 mϪ/Ϫ, K14-⌬hϩ mice gradually developed the DEB phenotype, including nail dystrophy, scarring on the paws, fusion of the digits, yellowish dental caries, and mild alopecia, characteristic features of human RDEB ( Figure 5, K-O). [13][14][15] It was difficult to distinguish the alopecia seen in the COL7 mϪ/Ϫ, K14-⌬hϩ mice from barbarism only from clinical appearance. However, the penetration of the alopecia is almost 100% in the COL7 mϪ/Ϫ, K14-⌬hϩ mice, whereas only a few wild-type littermates that were kept in the same condition showed barbarism.…”
Section: Col7a1 Humanized Mice 2513mentioning
confidence: 99%
“…The p.G2366A mutation interrupts a continuous stretch of 16 Gly-X-Y repeats within the collagenous domain of COLVII, but its damaging effect on triple helix assembly is not evident at the heterozygous state [10]. Two similar mutations, p.G2366S and p.G2366C, resulted in mild recessive DEB forms when combined with other mutations in the second allele, but another change in the same codon, p.G2366V, caused dominant EBP [11,12,13]. In the latter family, however, disease onset occurred during the twenties in 2 subjects while an additional heterozygous carrier of the mutation lacked DEB symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…During the course of COL7A1 DEB patient mutational analysis (Sawamura et al 2005) we found a unique GS mutation which was associated with retention of type VII collagen in keratinocytes. Some, but not all, GS COL7A1 mutations result in intracellular accumulation of collagen VII (Hammami-Hauasli et al 1998;Shimizu et al 1999).…”
Section: Introductionmentioning
confidence: 99%